Analisis Pengaruh Pengetahuan Pajak dan Motivasi Terhadap Minat Mahasiswa Berkarir di Bidang Perpajakan: Studi Kasus Mahasiswa Program Studi Akuntansi Universitas Teknologi Digital - Gina Yuniarti; Meilani Purwanti (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of tax knowledge and motivation on students’ career interest in the field of taxation. The background of this research is the low interest of accounting students to pursue careers in the tax sector. The research was conducted on students of the Accounting Study Program at Digital Technology University using a quantitative approach. Data were collected through questionnaires distributed to 159 respondents and analyzed using multiple linear regression. The results show that partially, tax knowledge has a positive and significant influence on students’ career interest, while motivation does not have a significant effect. However, simultaneously, tax knowledge and motivation have a positive and significant influence on students' career interest in taxation. These findings provide important implications for educational institutions and policymakers to enhance understanding and motivational factors in order to prepare qualified future tax professionals